The prevalence and nutritional implications of fast food consumption among patients receiving hemodialysis - Butt, Saud; Leon, Janeen B; David, Carol L; Chang, Henry; Sidhu, Sanbir; Sehgal, Ashwini R (Journal of renal nutrition, 2007)
Fast food consumption has increased dramatically in the general population over the last 25 years. However, little is known about the prevalence and nutritional implications of fast food consumption among patients receiving hemodialysis. By using a cross-sectional study design, we obtained data on fast food consumption and nutrient intake (from four separate 24-hour dietary recalls) and nutritional parameters (from chart abstraction) for 194 randomly selected patients from 44 hemodialysis facilities in northeast Ohio. Eighty-one subjects (42%) reported consuming at least one fast food meal or snack in 4 days. Subjects who consumed more fast food had higher kilocalorie, carbohydrate, total fat, saturated fat, and sodium intakes. For example, kilocalorie per kilogram intake per day increased from 18.9 to 26.1 with higher frequencies of fast food consumption (P = .003). Subjects who consumed more fast food also had higher serum phosphorus levels and interdialytic weight gains. Fast food is commonly consumed by patients receiving hemodialysis and is associated with a higher intake of kilocalories, carbohydrates, fats, and sodium and adverse changes in phosphorus and fluid balance. Further work is needed to understand the long-term benefits and risks of fast food consumption among patients receiving hemodialysis.